Integrasi Islam dan Sains (Analisis Problematika dan Level Integrasi) - Egisca Mauly Sagita; Thasa Oktafiana; Tasya Aulia Arsul Masfufah; Oktaviani Putri Melinda; Alfina Wildatul Fitriyah (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
The separation of Islam and science resulted in the decline of Muslim civilization, on the one hand, and an existential crisis on the other. The integration of fatigue can lead Muslims to achievement as well as moral perfection. Efforts to integrate Islam and science have been initiated by Muslim thinkers through the dewesternization of science, the Islamization of science, the science of Islam, and others. Lagging behind in the fields of science and technology is a problem that has emerged since the end of the Middle Ages (18th century AD), so that since then Muslims have been infected with "catching-up syndrome" which has caused negative responses and resistance from many groups. This is mainly due to theological concerns, cultural effects and ecological crises. At least the prominent resistance in the form of movements can be divided into three (1) restorationist movements, (2) Bucailis movements and (3) fundamentalist movements. The response to these efforts is counterproductive with efforts to catch up and at the same time with the spirit of Islam that upholds science. Therefore, a more basic study is needed on a proportional and harmonious integration integration framework. The integration of these values touches three levels (1) the level of scientific mental development, (2) The level of world view, namely establishing an Islamic world viewkrisis of the universe such, (3) Orientation level.